Discovery of surrogate agonists for visceral fat Treg cells that modulate metabolic indices in vivo - Ricardo A Fernandes; Chaoran Li; Gang Wang; Xinbo Yang; Christina S Savvides; Caleb R Glassman; Shen Dong; Eric Luxenberg; Leah V Sibener; Michael E Birnbaum; Christophe Benoist; Diane Mathis; et al. (eLife, 2020)
T regulatory (Treg) cells play vital roles in modulating immunity and tissue homeostasis. Their actions depend on TCR recognition of peptide-MHC molecules; yet the degree of peptide specificity of Treg-cell function, and whether Treg ligands can be used to manipulate Treg cell biology are unknown. Here, we developed an Ab-peptide library that enabled unbiased screening of peptides recognized by a bona fide murine Treg cell clone isolated from the visceral adipose tissue (VAT), and identified surrogate agonist peptides, with differing affinities and signaling potencies. The VAT-Treg cells expanded in vivo by one of the surrogate agonists preserved the typical VAT-Treg transcriptional programs. Immunization with this surrogate, especially when coupled with blockade of TNFα signaling, expanded VAT-Treg cells, resulting in protection from inflammation and improved metabolic indices, including promotion of insulin sensitivity. These studies suggest that antigen-specific targeting of VAT-localized Treg cells could eventually be a strategy for improving metabolic disease.